Increasing Taxpayer Compliance Through The Implementation of Tax Management Models - Rustan Rustan; Andi Arifwangsa Adiningrat; Idrawahyuni Idrawahyuni (International Journal of Economics Development Research (IJEDR), 2023)
Taxpayer non-compliant behavior can indeed be one of the main causes of tax violations. A tax gap occurs when there is a difference between the amount of tax that a taxpayer should pay and the amount of tax that is actually paid. Efforts that can be made to increase taxpayer compliance with the approach that has been implemented is the application of a tax management model which is designed to help taxpayers understand their obligations, manage tax payments, and minimize the risk of non-compliance. This research aims to determine the tax management model that is implemented can affect taxpayer compliance. The data analysis method in this research uses qualitative methods, this method is to answer the problem formulation. The data collection technique in this research was carried out by distributing questionnaires and interviews with informant sources at the Massaniga & Partners Tax Consultant Office. The research results show that the tax management model has an effective impact in increasing taxpayer compliance.